Changes in host–parasitoid food web structure with elevation. (20th October 2014) - Maunsell, Sarah C.; Kitching, Roger L.; Burwell, Chris J.; Morris, Rebecca J.; Webb, Tom
Summary Gradients in elevation are increasingly used to investigate how species respond to changes in local climatic conditions. Whilst many studies have shown elevational patterns in species richness and turnover, little is known about how food web structure is affected by elevation. Contrasting responses of predator and prey species to elevation may lead to changes in food web structure. We investigated how the quantitative structure of a herbivore‐parasitoid food web changes with elevation in an Australian subtropical rain forest. On four occasions, spread over 1 year, we hand‐collected leaf miners at twelve sites, along three elevational gradients (between 493 m and 1159 m a.s.l). A total of 5030 insects, including 603 parasitoids, were reared, and summary food webs were created for each site. We also carried out a replicated manipulative experiment by translocating an abundant leaf‐mining weevil Platynotocis sp., which largely escaped parasitism at high elevations (≥900 m a.s.l.), to lower, warmer elevations, to test if it would experience higher parasitism pressure. We found strong evidence that the environmental change that occurs with increasing elevation affects food web structure. Quantitative measures of generality, vulnerability and interaction evenness decreased significantly with increasing elevation (and decreasing temperature), whilst elevation did not have a significant effect on connectance. Mined plant composition also had a significant effect on generality and vulnerability, but not on interaction evenness. Several relatively abundant species of leaf miner appeared to escape parasitism at higher elevations, but contrary to our prediction, Platynotocis sp. did not experience greater levels of parasitism when translocated to lower elevations. Our study indicates that leaf‐mining herbivores and their parasitoids respond differently to environmental conditions imposed by elevation, thus producing structural changes in their food webs. Increasing temperatures and changes in vegetation communities that are likely to result from climate change may have a restructuring effect on host–parasitoid food webs. Our translocation experiment, however, indicated that leaf miners currently escaping parasitism at high elevations may not automatically experience higher parasitism under warmer conditions and future changes in food web structure may depend on the ability of parasitoids to adapt to novel hosts.